Hello!
To solve algebraic equations, we need to first, simplify the common terms, and secondly use SADMEP. SADMEP is strictly used to solve algebraic equations, and is used like PEMDAS. SADMEP is an acronym for subtract, addition, division, multiplication, exponents, and parentheses.
25 - 4x = 15 - 3x + 1 - x (simplify the common terms)
25 - 4x = 16 - 4x (subtract 16 from both sides)
9 - 4x = -4x (add 4x to both sides)
9 = 0 → This means that there is no solutions.
Therefore, this equation has no solutions, which are contradictions because those are the equations with no solution.
Equation: 5x² - 3x - 14
= 5x² - 10x + 7x - 14
= 5x(x - 2) 7(x - 2)
= (5x + 7)(x - 2)
In short, Your Answer would be: Option B
Hope this helps!
Answer: First option is correct.
Step-by-step explanation:
Since we have given that
![6x^3+6](https://tex.z-dn.net/?f=6x%5E3%2B6)
Now, by factorising , we get
![6x^3+6\\=6(x^3+1)](https://tex.z-dn.net/?f=6x%5E3%2B6%5C%5C%3D6%28x%5E3%2B1%29)
Now, we use the formula i.e.
![a^3+b^3=(a+b)(a^2-ab+b^2)](https://tex.z-dn.net/?f=a%5E3%2Bb%5E3%3D%28a%2Bb%29%28a%5E2-ab%2Bb%5E2%29)
By using this, we get ,
![6(x^3+1)\\=6(x+1)(x^2-x+1)](https://tex.z-dn.net/?f=6%28x%5E3%2B1%29%5C%5C%3D6%28x%2B1%29%28x%5E2-x%2B1%29)
So,
![(x+1) \text{ is the factor of }6x^3+6.](https://tex.z-dn.net/?f=%28x%2B1%29%20%5Ctext%7B%20is%20the%20factor%20of%20%7D6x%5E3%2B6.)
It would be much easier if you attached a table. Anyway I know what you need to do. Just make an equation and put the numbers from the table given you in the task. And you'll solve it.